TRANSFORMASI BIMBINGAN DAN KONSELING DAN IMPLIKASINYA BAGI PENDIDIKAN SEKOLAH DASAR - Nurhalisa, Siti; Sunarti, Titi; Vitrianti, Vivit; Aliyah, Putri Robiatul; Silvi, Silvi (Jurnal Merah Putih Sekolah Dasar, 2025)
Guidance and counseling (BK), is a field of science that studies self-development, potential, problem solving, and decision-making in the individual itself with the guidance of a counselor / teacher. The first counseling guidance counseling was in America in the early 20th century, pioneered by Frank Parsons, known as the Father of "career guidance". He founded the Boston Vocational School in 1908 to help individuals find jobs that match their interests and talents. In Indonesia, guidance and counseling began to be known in the 1960s, using the latest educational impacts and western psychology. BK is integrated into the formal education system to help students find their interests, talents, personal, social and career, BK in Indonesia continues to develop over time and adapt to current conditions. The history of BK reflects a transformation based on simple methods to complex approaches and structured scientific approaches, achieving individuals to reach their maximum potential.